Correlation between thyroxin hormone level, bilirubin and uric acid in diabetic subjects - Mathur, Rajendra Dutt; Gupta, Rameshwar Prasad; Gupta, Deepak; Bhargav, Ajay Kumar; Mathur, Reenika (International Journal of Research in Medical Sciences, 2018)
Background: Levels of thyroxin hormone along with T3, TSH and other markers such as uric acid, bilirubin and glucose are important in diagnosis and medical management of diabetes mellitus and thyroid disorder. Relationship between these parameters are important in both diabetes mellitus and Thyroid gland disease, as both disorders are increasing very fast in Indian population. Present study aimed to analyzed T3, T4, TSH, uric acid and bilirubin in Haroti Region of Jhalawar, Rajasthan in diabetic and non diabetic subjects. Methods: One hundred diabetes mellitus subjects and 100 healthy control subjects were analyzed for determination of thyroxin, T3, TSH, uric acid and bilirubin by commercial kit method. Results: One hundred subjects of diabetes mellitus between age 30-60 years male and female were analyzed. It was observed significantly T3 <0.001 T4 <0.001 TSH <0.001 bilirubin <0.01 in diabetic subjects and found to be significant when compared in both groups. However, uric acid level insignificant in both patients and control groups. Conclusions:This study demonstrated that thyroxin hormone with T3, TSH and bilirubin and uric acid, are important parameters and their values are significant when compared with healthy subjects in diabetes mellitus and thyroid disorder.